O ensino de língua portuguesa em São Paulo na segunda metade do século XX: um caminho historiográfico - Iório, Patrícia Leite Di (2007)
The present study is part of História e Descrição da Língua Portuguesa Research Line, particularly in the discussions of the research group on Historiography of Portuguese Language (GPeHLP) in IP-PUC/SP (Research Institute of Pontifícia Universidade Católica de São Paulo). It represents a historiographic view of Portuguese Language Teaching in the second half of the twentieth century through the Leis de Diretrizes e Bases da Educação Nacional (LDBEN) and the Didacts Resources, introduced by the State of São Paulo government. Our aim was to rebuild the linguistic and pedagogic progress of the Portuguese Language, in other words, to know the ways taken by the official documents since the establishment of Linguistics in Brazil. We also wanted to examine the changes that the linguistic theories brought to the mother tongue and to the pedagogic practices. Besides, we wanted to point the way the government has seen the teacher, as it is the organizer and the publisher of these documents. In order to make this research effective, we made use of three categories of analysis, established after the reading of the primary sources and we followed the principles of Historiography of Linguistics and of the History of Present. Thus, at first, we could contextualize the period and then we rebuilt and elucidated the texts of the documents to adequate them to the LDBEN/96 and to the Parâmetros Curriculares Nacionais (PCN-LP/98). After the analysis, we found out that the teaching of mother tongue can be contextualized in three moments that can be related to three different conceptions of language, and that the changes in language paradigms were fundamental to elaborate material to the establishment of a bridge between linguistic knowledge and teaching practice. We still noticed that the publication of these materials always characterized teachers as professionals without the necessary formation to develop their function, so that they had to be guided or that some proposals and subsidies had to be imposed to them